Directory of research and training institutions and organizations on economic and social development and planning in Asia and the Pacific. (Asian and Pacific Development Centre : Association of Develoment Research and Training Institutes of Asia and the Pacific, 1995)
"The Directory of Research and Training Institutions and Organizations Economic and Social Development and Planning in Asia and the Pacific contains information on 793 departments, institutions and organizations in 29 countries in the Asia and Pacific region engaged in a very wide range of economic and social activities which have a bearing on the process and problems of economic and social development planning." The areas covered include: agriculture, development policy, economic condition, economic research and systems, energy and environmental policy, external debt, employment, international cooperatives and relations, industry and trade, management, population, public administration, regional development, rural development societies, social policy and planning, social services, structural adjustments and women in development. The primary aim of the directory is to enable users to locate institutions and organizations in the field of economic and social development. The primary aim of the dictionary is to enable users to locate institutions and organizations in the field of economic and social development and planning and thereby facilitate networking. It is divided into two sections: the first section contains the profile of the institutions and organizations arranged alphabetically by country, and within country, arranged alphabeticlly by name of institutions. The second section of the Directory contains the indices which enable quick search to the entries in the first section.